2009
DOI: 10.1183/09031936.00045209
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic M3 receptor stimulation increases cigarette smoke-induced IL-8 secretion by human airway smooth muscle cells

Abstract: Acetylcholine is the primary parasympathetic neurotransmitter in the airways and is known to cause bronchoconstriction and mucus secretion. Recent findings suggest that acetylcholine also regulates aspects of remodelling and inflammation through its action on muscarinic receptors.In the present study, we aimed to determine the effects of muscarinic receptor stimulation on cytokine production by human airway smooth muscle cells (primary and immortalised cell lines). The muscarinic receptor agonists carbachol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 46 publications
(68 reference statements)
4
43
0
1
Order By: Relevance
“…ACh may contribute to neutrophilia as it was shown to stimulate the release of neutrophil chemotactic activity from isolated alveolar macrophages [16] and from isolated sputum cells of COPD patients [42]. Furthermore, activation of muscarinic receptors expressed in airway structural cells, including bronchial epithelial [17] and ASM cells [19], may also contribute to neutrophil sequestration in the lungs by inducing or augmenting IL-8 release by these cells. In addition, the high capacity of neutrophils to synthesise ACh [43] implies that neutrophilia may result in increased non-neuronal ACh release in the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACh may contribute to neutrophilia as it was shown to stimulate the release of neutrophil chemotactic activity from isolated alveolar macrophages [16] and from isolated sputum cells of COPD patients [42]. Furthermore, activation of muscarinic receptors expressed in airway structural cells, including bronchial epithelial [17] and ASM cells [19], may also contribute to neutrophil sequestration in the lungs by inducing or augmenting IL-8 release by these cells. In addition, the high capacity of neutrophils to synthesise ACh [43] implies that neutrophilia may result in increased non-neuronal ACh release in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, increased ChAT expression was found in lung fibroblasts from smokers and COPD patients [15]. Muscarinic M 3 receptor stimulation has been shown to increase the release of neutrophil chemotactic activity by alveolar macrophages [16], induce interleukin (IL)-8 release by bronchial epithelial cells [17] and monocytes [18], and augment cigarette smoke-induced IL-8 release by ASM cells [19]. In addition, muscarinic receptor agonists were shown to stimulate or potentiate proliferation of lung fibroblasts [20] and ASM cells [21], as well as lung fibroblast collagen synthesis [22].…”
mentioning
confidence: 99%
“…This is referred to as non-neuronal acetylcholine and may contribute to airway inflammation [9][10][11]. Indeed, in vitro studies have revealed a variety of effects of acetylcholine on these cell types [11], including an induced release of the potent neutrophil chemoattractants IL-8 and leukotriene (LT)B 4 from airway epithelial, smooth muscle and inflammatory cells [12][13][14][15]. Recent evidence from in vivo studies also demonstrated a pro-inflammatory role for acetylcholine under pathophysiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these findings indicate that acetylcholine, derived from the vagal nerve and from non-neuronal origins such as the airway epithelium, may induce cell responses associated with airway wall remodelling and trigger proinflammatory Cytokines as IL-6 and IL-8 release in [9] by structural cells of the airways, including the airway smooth muscle itself. In addition, muscarinic receptors regulate proliferative and proinflammatory functions of the airway smooth muscle as mentioned in references [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, muscarinic receptors regulate proliferative and proinflammatory functions of the airway smooth muscle as mentioned in references [9,10].…”
Section: Introductionmentioning
confidence: 99%